1999
DOI: 10.1029/1999jd900085
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of boreal forest regional water flux and net primary production simulations to sub‐grid‐scale land cover complexity

Abstract: Abstract. We use a general ecosystem process model (BIOME-BGC) coupled with remote sensing information to evaluate the sensitivity of boreal forest regional evapotranspiration (ET) and net primary production (NPP) to land cover spatial scale. Simulations were conducted over a 3 year period (1994)(1995)(1996) d-•). Factors responsible for differences in scaling behavior between ET and NPPincluded compensating errors for ET calculations and boreal forest spatial and temporal NPP complexity. Careful considerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 56 publications
2
36
0
Order By: Relevance
“…Less than 20% of the days at either site required filling in missing data with measurements from elsewhere. The effectiveness of the model itself has been documented to some degree with regard to NPP in boreal (Kimball et al, 2000(Kimball et al, , 1999(Kimball et al, , 1997 and temperate (Running, 1994) forests. The used of binned GPP data at the tower makes it difficult to closely evaluate the effectiveness of modeled GPP responses to day-to-day variation in meteorology but the model output is clearly tracking most of the oscillations during the growing season.…”
Section: Assessment Of Bigfoot Gpp Productsmentioning
confidence: 99%
See 3 more Smart Citations
“…Less than 20% of the days at either site required filling in missing data with measurements from elsewhere. The effectiveness of the model itself has been documented to some degree with regard to NPP in boreal (Kimball et al, 2000(Kimball et al, , 1999(Kimball et al, , 1997 and temperate (Running, 1994) forests. The used of binned GPP data at the tower makes it difficult to closely evaluate the effectiveness of modeled GPP responses to day-to-day variation in meteorology but the model output is clearly tracking most of the oscillations during the growing season.…”
Section: Assessment Of Bigfoot Gpp Productsmentioning
confidence: 99%
“…The process model employed for scaling GPP was the Biome-BGC model (Kimball, Keyser, Running, & Saatchi, 2000;Kimball, Running, & Saatchi, 1999;Kimball, Thornton, White, & Running, 1997;Running, 1994;Running & Hunt, 1993). A version similar to that used in this study has been applied and tested in temperate (Coops, Waring, Brown, & Running, 2001;Running, 1994) and boreal (Kimball et al, 1997(Kimball et al, , 1999 forests.…”
Section: Process Model Applicationmentioning
confidence: 99%
See 2 more Smart Citations
“…However, unresolved heterogeneity in vegetation properties in these ecosystems can be significant; Kimball et al [1999], for instance, found that subpixel-scale land cover complexity in boreal forests could lead to annual net primary production (NPP) errors of more than 14% using an ecosystem process model. In another study, Bonan et al [1993] showed that landscape heterogeneity in coniferous forests had a highly nonlinear effect on sensible heat and evapotranspiration calculations, with errors as high as 46% and 15%, respectively.…”
Section: Introductionmentioning
confidence: 99%